2012
DOI: 10.1542/peds.2011-1762
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Reactions to Foods in Preschool-Aged Children in a Prospective Observational Food Allergy Study

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Infants and children with diagnosed food allergy are at risk for acute, potentially life-threatening symptoms. Limited data are available on the frequency, severity, and circumstances of reactions and caretaker medical response. WHAT THIS STUDY ADDS:This study describes food allergy reaction frequency, circumstances, and response. Pitfalls that may inform improved anticipatory guidance included lack of vigilance, misreading ingredient labels, allergen cross-contact, nonaccidental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
171
3
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 241 publications
(187 citation statements)
references
References 31 publications
6
171
3
7
Order By: Relevance
“…1,3,8,35 Many patients and caregivers fail to carry EAs consistently or to use them when anaphylaxis occurs, even for severe symptoms, including throat tightness, difficulty breathing, wheezing, and loss of consciousness. 41,45,46 People may have different reasons for not using EAs, including failure to recognize anaphylaxis symptoms, spontaneous recovery from a previous anaphylactic episode and the assumption that this will happen in every episode, reliance on oral H 1 -antihistamines and/ or inhaled bronchodilators, no EA available, fear of needles, and concerns about epinephrine adverse effects. 41, 45 -48 Many parents fear using an EA because they worry about hurting or injuring their child or a bad outcome.…”
Section: Using Easmentioning
confidence: 99%
See 1 more Smart Citation
“…1,3,8,35 Many patients and caregivers fail to carry EAs consistently or to use them when anaphylaxis occurs, even for severe symptoms, including throat tightness, difficulty breathing, wheezing, and loss of consciousness. 41,45,46 People may have different reasons for not using EAs, including failure to recognize anaphylaxis symptoms, spontaneous recovery from a previous anaphylactic episode and the assumption that this will happen in every episode, reliance on oral H 1 -antihistamines and/ or inhaled bronchodilators, no EA available, fear of needles, and concerns about epinephrine adverse effects. 41, 45 -48 Many parents fear using an EA because they worry about hurting or injuring their child or a bad outcome.…”
Section: Using Easmentioning
confidence: 99%
“…41, 45 -48 Many parents fear using an EA because they worry about hurting or injuring their child or a bad outcome. 46,47 Unintentional injections into digits and other body parts, with or without injuries, 48 and lacerations incurred when an inadequately restrained child moves during the injection are reported from pen-type EAs. 49 Teenagers are at increased risk of death in anaphylaxis 16 -18 because of high-risk behaviors, including ethanol and/or recreational drug use, failure to recognize triggers, denial of symptoms, and failure to carry their EAs and inject epinephrine promptly when anaphylaxis occurs.…”
Section: Using Easmentioning
confidence: 99%
“…While much childhood food allergy is outgrown, a substantial proportion of even milk and egg allergy persists into adulthood, and some food allergies, such as peanut, tree nuts, and shellfish, are usually persistent (1). Reported rates of reaction due to accidental exposure vary widely, from 5% per year to 58% per five years for peanut (2,3) and up to 80% per year for milk (4). Although mortality from food-related anaphylaxis is rare, estimated to be approximately 1.8 per million person-years among foodallergic subjects (5), fear of accidental reactions and social effects of avoidance diets contribute to significantly impaired quality of life for food-allergic children and their caregivers (6).…”
Section: Introductionmentioning
confidence: 99%
“…(1) Peanuts and tree nuts are the most common triggers of severe and fatal food-induced anaphylactic reactions, (2;3) and peanut allergy is less commonly outgrown than allergy to other major food allergens; thus significant, lifelong changes in dietary habits are required. Given the ever-present fear of severe allergic reactions from accidental ingestions and food product contamination, (4)(5)(6) the potential for severe or fatal reactions, (3;7) the need for strict elimination diets and difficulty interpreting food labels, (8;9) a diagnosis of food allergy has significant medical, nutritional and psychosocial implications for affected individuals and families. (10)(11)(12)(13)(14) Additionally, there is a substantial economic impact, as investigators have also reported increased health care expenditures associated with food allergy.…”
Section: Introductionmentioning
confidence: 99%